Qualitative evaluation of MR images for assessing placenta accreta spectrum disorders in patients with placenta previa: A pilot validation study. Issue 146 (January 2022) - Maurea, Simone; Verde, Francesco; Mainenti, Pier Paolo; Barbuto, Luigi; Iacobellis, Francesca; Romeo, Valeria; Liuzzi, Raffaele; Raia, Giorgio; De Dominicis, Gianfranco; Santangelo, Claudio; Romano, Luigia; Brunetti, Arturo
Highlights: MRI is a reproducible tool for the detection of PAS in high-risk patients. Dark bands, focal interruption of myometrial border, abnormal vascularity. At least two abnormal MRI signs is a useful method to assess PAS. Placental MRI for PAS evaluation requires imaging expertise and methodology. Abstract: Purpose: To validate a qualitative imaging method using magnetic resonance (MR) for predicting placental accreta spectrum (PAS) in patients with placenta previa (PP). Method: Two MR imaging methods built in our previous experience was tested in an external comparable group of sixty-five patients with PP; these methods consisted of presence of at least one (Method 1) or two (Method 2) of the following abnormal MR imaging signs: intraplacental dark bands, focal interruption of myometrial border and abnormal placental vascularity. Three groups of radiologists with different level of expertise evaluated MR images: at least 5 years of experience in body imaging (Group 1); at least 10 (Group 2) or 20 (Group 3) years of experience in genito-urinary MR. While radiologists of Group 1 routinely evaluated MR images, those of Groups 2 and 3 used both Methods 1 and 2. Results: A significant (p < 0.005) difference was found between the diagnostic accuracy values of imaging evaluation performed by Group 3 using Method 1 (63%) and Method 2 (89%); of note, the accuracy of Method 2 by Group 3 was also significantly (p < 0.005) higher compared to that of both Methods 1 (46%) and 2 (63%) by Group 2 as well as to that of the routine evaluation by Group 1 (60%). Conclusions: The qualitative identification of at least two abnormal MR signs (Method 2) represents an accurate method for predicting PAS in patients with PP particularly when this method was used by more experienced radiologists; thus, imaging expertise and methodology is required for this purpose.